Inhibition of Renal Tubular Epithelial Mesenchymal Transition and Endoplasmic Reticulum Stress-Induced Apoptosis with Shenkang Injection Attenuates Diabetic Tubulopathy - Wang, Wen-Wen; Liu, Ying-Lu; Wang, Mei-Zi; Li, Huan; Liu, Bu-Hui; Tu, Yue; Yuan, Can-Can; Fang, Qi-Jun; Chen, Jia-Xin; Wang, Jie; Fu, Yan; Wan, Zi-Yue; et al. (Frontiers in Pharmacology, 2021)
Background: The proximal renal tubule plays a critical role in diabetic kidney disease (DKD) progression. Early glomerular disease in DKD triggers a cascade of injuries resulting in renal tubulointerstitial disease. These pathophysiological responses are collectively described as diabetic tubulopathy (DT). Thus, therapeutic strategies targeting DT hold significant promise for early DKD treatment. Shenkang injection (SKI) has been widely used to treat renal tubulointerstitial fibrosis in patients with chronic kidney disease in China. However, it is still unknown whether SKI can alleviate DT. We designed a series of experiments to investigate the beneficial effects of SKI in DT and the mechanisms that are responsible for its effect on epithelial-to-mesenchymal transition (EMT) and endoplasmic reticulum (ER) stress-induced apoptosis in DT. Methods: The modified DKD rat models were induced by uni-nephrectomy, streptozotocin intraperitoneal injection, and a high-fat diet. Following the induction of renal injury, these animals received either SKI, rosiglitazone (ROS), or vehicle, for 42 days. For in vitro research, we exposed NRK-52E cells to high glucose (HG) and 4-phenylbutyric acid (4-PBA) with or without SKI or ROS. Changes in parameters related to renal tubular injury and EMT were analyzed in vivo. Changes in the proportion of apoptotic renal tubular cells and ER stress, and the signaling pathways involved in these changes, were analyzed both in vivo and in vitro. Results: SKI and ROS improved the general condition, the renal morphological appearance and the key biochemical parameters, and attenuated renal injury and EMT in the rat model of DKD. In addition, SKI and ROS alleviated apoptosis, inhibited ER stress, and suppressed PERK-eIF2α-ATF4-CHOP signaling pathway activation both in vivo and in vitro. Notably, our data showed that the regulatory in vitro effects of SKI on PERK-eIF2α-ATF4-CHOP signaling were similar to those of 4-PBA, a specific inhibitor of ER stress. Conclusion: This study confirmed that SKI can alleviate DT in a similar manner as ROS, and SKI achieves this effect by inhibiting EMT and ER stress-induced apoptosis. Our findings thereby provide novel information relating to the clinical value of SKI in the treatment of DT.